Helicobacter pylori Induces Increased Expression of the Vitamin D Receptor in Immune Responses. Issue 1 (4th November 2013) - Guo, Lihua; Chen, Wenguo; Zhu, Huatuo; Chen, Yu; Wan, Xingyong; Yang, Ningmin; Xu, Shuhua; Yu, Chaohui; Chen, Lihua
Abstract Background Vitamin D receptor (VDR) is a member of the nuclear receptor family of transcription factors that play a critical role in innate immunity. This study examined the role of VDR in gastric innate immune defence against the gastric pathogen Helicobacter pylori. Materials and Methods Seventeen H. pylori‐infected patients and sixteen controls participated in the study. The GES‐1 cells were transfected with siRNA or incubated with or without 1α, 25(OH)2D3 (100 nmol/L) then infected with H. pylori. VDR, cathelicidin antimicrobial protein (CAMP), and cytokine mRNA expression levels in normal and H. pylori‐infected gastric mucosa and GES‐1 cells was determined by qRT‐PCR and correlated with the histopathologic degree of gastritis. Bactericidal activity was measured by using a colony‐forming unit assay. Results Vitamin D receptor mRNA expression levels were significantly upregulated in H. pylori‐infected patients and positively correlated with chronic inflammation scores. There was a significant positive correlation between VDR and CAMP mRNA expression in H. pylori‐positive gastric mucosa. VDR siRNA reduced H. pylori‐induced CAMP production and conversely increased IL‐6 and IL8/CXCL8 expression levels. The vitamin D agonist 1α, 25(OH)2D3 increased CAMP expression and reduced cytokine activation in GES‐1 cells infected with H. pylori. 1α, 25(OH)2D3 could enhance the intracellular killing of the replicating bacteria, but the presence of siVDR and siCAMP led to a decline in its bactericidal ability. Conclusions The expression of VDR and CAMP in the gastric epithelium is up‐regulated in the case of H. pylori infection; thus, VDR plays an important role in gastric mucosa homeostasis and host protection from H. pylori infection.